Social policy and poverty in east Asia [ the role of social security - Midgley, James; Tang, Kwong-Leung (Routledge research on public and social policy in Asia, 2009)
This book looks at the role of social policy, particularly social security, in addressing the ongoing challenge of poverty in East Asia despite the region?s spectacular experience of economic growth in decent decades.